Burnout syndrome in Veterinary Medicine students - Puertas-Neyra, Kevin (2020)
Academic Burnout Syndrome is defined as an inappropriate response to stressors added to inefficient support systems, which damages the academic, physical and mental performance of students. This study aimed to determine the prevalence and factors associated with Burnout Syndrome in Veterinary Medicine students at the Universidad Peruana Cayetano Heredia (Lima, Peru). The research was descriptive and observational. Data collection was carried out using the Maslach Burnout Inventory - Student Survey scale and a sociodemographic survey. Statistical analysis was performed using the Chi square test. A prevalence of Burnout Syndrome of 32.3% (87/269) was found. It was determined that 58.7% (n=158) and 14.1% (n=38) of the students presented severe levels of emotional exhaustion and cynicism, respectively, while 46.1% (n=124) presented low levels of academic self-efficacy. A significant association was found between the year of study, gender, living arrangement, hours of sleep and sports practice with the level of emotional exhaustion. The year of study and tobacco use were associated with the level of cynicism. Furthermore, a significant association was found between sports, gastrointestinal and psychosomatic disorders with the presence of Burnout Syndrome. There is a high prevalence of Burnout Syndrome among Veterinary Medicine students, both in multidimensional and dichotomous evaluation, which is associated with different sociodemographic factors.